POTRET PERILAKU ANAK KORBAN PERCERAIAN ORANG TUA DI DUSUN BUMIAYU - Wahyu Andhi Kristian; Steaven Octavianus; Dwi Novita Sari (SAGACITY : Journal of Theology and Christian Education, 2020)
The purpose of this research is to elaborate the children of divorced parents’ behaviors in Bumiayu, Sumogawe, Getasan, Semarang. The respondents for this research are six children of divorced parents from Christian Families. They are three females and males, with ages ranged between 14 to 23. Data compilation is conducted through interviews and observations This research is using qualitative and descriptive analysis. The research concludes that divorce could affect children’s behavior in several different ways, there are those who become closed personality; those who experiences decline in their academic performance; and even those who attain better academic achievements and become independent. The effects appearing as a result of a divorce on children depend on the parents’ understanding towards the feelings of the children and their upbringing nurtutre.